Recent Developments in Burial Alternatives inLight of Islamic law Principles: Human Composting as a Case Study (Damascus University Journal for legal sciences, 2024)
this research investigates the recent developments in burial alternativeswithin what is called the "green burial" movement, which calls for environmentalsustainability in to human death practices. It focuses on human composting, a processthat transforms human remains into nutrient-rich compost within weeks. Thestudy aims to examine the legality of these recent developments from an Islamic law perspective, considering both the principles and objectives of Islamic law.The research employs a descriptive approach to explain the nature andmechanisms of these new methods, an analytical approach to evaluate theJustifications of their proponents, and an rooted and deductive approachto ground the issue in the established roots of Islamic law.The study is divided into three main sections:Defining Recent Developments in Burial Alternatives and Human Composting: This section introduces the various alternatives to traditional burial, including human composting, and explains the process involved.The Parameters of Burial Rulings in Islamic law:This section explores the Islamic legal principles governing burial, sanctity (inviolability) of the human body both in life and emphasizing theafter death.The Ruling on Recent Developments in Burial Alternatives: Thissection analyzes the permissibility of various alternatives, includinghuman composting, in light of Islamic law.   The study concludes that:Islamic law prohibits any burial alternative that involves burning dismembering, crushing bones, or dissolving flesh. This prohibition of the human body. Consequently sanctity stems from the establishe dmethods such as liquid cremation and cryomation are forbidden.Human composting, if it involves crushing bones, is explicitly prohibited by Islamic texts. Even if it does not involve bone crushing, the study concludes that it fundamentally contradicts the principles and objectives of Islamic law.This is because it undermines the inherent dignity of the human being and conflicts with the objectives of  benefiting the deceased through the prayers of visitors and serving as a reminder and lesson for living.Green burial methods that involve burying the body in the ground without embalming or a coffin are compatible with Islamic teachings.This applies whether the body is wrapped in a biodegradable shroud or similar material, as long as it is placed in the ground in a dignified manner and covered with its components.Islamic teachings on dealing with the deceased's body strike a balance between protecting the environment, respecting and honoring the deceased, and fulfilling the purpose of remembering death and reviving faith in the afterlife.
Keywords: Burial Alternatives; Human Composting; Islamic Burial; Green Burial; Recent Developments in Burial